2022
DOI: 10.1371/journal.pone.0275361
|View full text |Cite
|
Sign up to set email alerts
|

Motivation is not enough: A qualitative study of lung cancer screening uptake in Australia to inform future implementation

Abstract: Introduction Participation in lung cancer screening (LCS) trials and real-world programs is low, with many people at high-risk for lung cancer opting out of baseline screening after registering interest. We aimed to identify the potential drivers of participation in LCS in the Australian setting, to inform future implementation. Methods Semi-structured telephone interviews were conducted with individuals at high-risk of lung cancer who were eligible for screening and who had either participated (‘screeners’)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…It was integral in overcoming other reported cultural, social, and structural or organizational policy barriers to screening. In our review, participants' lack of awareness of lung cancer screening was frequently reported, i.e., in 17 articles [28,[30][31][32][33][36][37][38][39]41,44,45,48,50,[57][58][59]. Participants often had not heard of lung cancer or chose not to be screened due to fear of a cancer diagnosis or concerns about cost, which affected their attitudes about lung cancer and their motivation to participate in lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was integral in overcoming other reported cultural, social, and structural or organizational policy barriers to screening. In our review, participants' lack of awareness of lung cancer screening was frequently reported, i.e., in 17 articles [28,[30][31][32][33][36][37][38][39]41,44,45,48,50,[57][58][59]. Participants often had not heard of lung cancer or chose not to be screened due to fear of a cancer diagnosis or concerns about cost, which affected their attitudes about lung cancer and their motivation to participate in lung cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Individual and interpersonal facilitators. Studies showed that individuals who were aware of early detection lung cancer screening [21][22][23][24][25][26][27][28][29][30][31], high perceived benefit [30,[42][43][44], motivation to quit smoking [32,33,38,45], provision of the mobile testing program and home test kits during COVID-19 [46], enthusiasm for lung cancer [28,[32][33][34]38,42,43,45,[47][48][49][50], a screening recommendation from a healthcare provider [30,33,38,45,51], and shared decisionmaking interaction between discussion [31,[52][53][54] were more supportive of screening and tended to be screened Table S1.…”
Section: Facilitators Of Lung Cancer Screening Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…We acknowledge that the resulting data do not reflect the perceptions of LCS participants. Our team has recently published a study of Australian participants in the International Lung Screening Trial, which found that individual PLOS ONE motivation to screen must be accompanied by strategies that enable opportunities and enhance individual's capabilities to screening for lung cancer [43]. Furthermore, our team is currently undertaking research to explore patient perceptions of barriers and facilitators to LCS program in focus groups with a diverse range of culturally diverse community members.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Previous research has shown reduced uptake of cancer screening consistently in underserved populations ( 26 - 28 ) and so demonstrates the need for newly implemented cancer screening programs to address the barriers to uptake in these populations from the early stages of planning a program. A recent Australian study examined participation factors in the International Lung Screening Trial using the COM-B model of behaviour change, citing capability, opportunity and motivation as factors to change behaviour ( 29 ). This study found that motivation alone may not be sufficient to change behaviour related to screening participation, unless capability (e.g., enhance people’s knowledge) and opportunity (e.g., convenient locations) are considered.…”
Section: Introductionmentioning
confidence: 99%